Renewrev : Stasiun pengisian daya cerdas untuk transformasi kendaraan listrik dengan energi terbarukan - Trisuwito, Margaretha Lintangsari; Menalang, Djibriel Frits Sualang; Almunir, Muhammad Farrell (Jurnal Teknologi Cerdas, 2025)
Indonesia faces challenges related to conventional electricity generation, including pollution and reliance on fossil fuels. This dependency leads to rising energy demand and soaring fuel prices. To address these issues, the government is promoting the dev elopment of renewable energy sources, such as solar and wind energy, to reduce conventional electricity use. The increasing adoption of electric vehicles (EVs) also drives the need for more charging stations. Innovations in electric vehicle technology and renewable  energy generation are essential for a sustainable future. This study compiles data from various sources to propose solutions, focusing on the design of hardware, system blocks, flowcharts, and use case diagrams for a project named SmartLink. The project aims to harness solar thermal and wind energy through technologies like turbine rotors, thermoelectric systems, and photovoltaic cells. Implementation of the SmartLink initiative will occur in three phases—capacity building, technical concept, and design—projected to last until early 2025.  By leveraging alternative renewable  energy, Indonesia  aims to mitigate its reliance on fossil fuels while supporting the growing demand for EV infrastructure.